2011
DOI: 10.1177/0194599811428118
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Central Apnea Index following Pediatric Adenotonsillectomy

Abstract: Children with OSA and mild CSA on preoperative PSG showed significant improvement in CAI following adenotonsillectomy. Future studies are needed to determine the clinical significance of CSA in children with OSA and to identify treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 8 publications
5
48
0
Order By: Relevance
“…Central apnoeas in children are associated with fluctuations in heart rate and blood pressure, and movement-induced central apnoeas (after movement or sigh) are more common in children with OSAS (class IV) [133]. There is one class IV study demonstrating reduction in the central apnoea index in children with OSAS post-adenotonsillectomy [134]. c, d) In a class III multicentre study, median, 10th and 90th percentile values of polysomnography parameters for 1-18 year-old healthy, non-obese children without symptoms of SDB were reported.…”
Section: 2mentioning
confidence: 99%
“…Central apnoeas in children are associated with fluctuations in heart rate and blood pressure, and movement-induced central apnoeas (after movement or sigh) are more common in children with OSAS (class IV) [133]. There is one class IV study demonstrating reduction in the central apnoea index in children with OSAS post-adenotonsillectomy [134]. c, d) In a class III multicentre study, median, 10th and 90th percentile values of polysomnography parameters for 1-18 year-old healthy, non-obese children without symptoms of SDB were reported.…”
Section: 2mentioning
confidence: 99%
“…Baldassari et al showed significant reduction in central apneas following tonsillectomy in children with both OSA and mild central apnea, a study that included some children with trisomy 21. 21 In contrast, Clark et al reported Cheyne-Stokes-like central apneas that persisted despite correction of the obstruction in a small cohort of subjects with trisomy 21 and OSDB. 19 While noninvasive ventilation with a mandatory rate might be expected to improve ventilation, it is not known whether further investigation, for example, with brain imaging to evaluate for abnormalities akin to Chiari malformation, is also necessary.…”
mentioning
confidence: 90%
“…Pediatric sleep laboratories and technicians are particularly adept at obtaining PSG studies in children with trisomy 21,18 but over a quarter of our subjects were unable to be studied using the entire montage with EEG, EMG, and EOG, because of lack of cooperation. Familiar surroundings and a simpler recording scheme make it likely that pulse oximetry may be successfully performed in a child's home rather than requiring the child to come to the sleep laboratory.…”
mentioning
confidence: 99%
“…In recent decades, the interest in childhood respiratory sleep disorders has increased considerably, and the number of scholarly publications on this matter has risen accordingly. Nevertheless, most of the literature has focused on reporting obstructive events, while there have been surprisingly few publications regarding the diagnosis and management of central sleep apnea (CSA) . With the exception of a recent review on the diagnosis, management, and pathophysiology of CSEA in children, there still remains a gap in the knowledge of the importance of central events in children, the central apnea index (CAI) threshold to be considered abnormal, and the range of CSA severity.…”
Section: Introductionmentioning
confidence: 99%